Aggression and locus of control in patients diagnosed with schizophrenia - Skowerska, Agnieszka; Czyżewski, Łukasz; Parnowska, Dorota; Wyzgał, Janusz; Silczuk, Andrzej (Frontiers in Psychiatry, 2025)
PurposeComparative analysis of data from patients diagnosed with schizophrenia and a control group from the healthy population regarding the level of aggression and anxiety, and the relationship between the locus of control, as well as analysis of the research hypothesis aimed at verifying whether higher levels of aggression occur in patients who place their sense of control outside themselves.Materials and methodsThe research conducted in this study is a questionnaire-based, clinical-control study. It was carried out between 2019 and 2022 and included 61 patients with the ICD-10 diagnosis of schizophrenia who met the defined criteria and agreed to participate in the research project. The study group consisted of patients who were hospitalized in day psychiatric wards and 24-hour rehabilitation wards. Work material for the study group was collected using such tools as the ICD-10 International Classification of Diseases, GAF scale, BPAQ Aggression Questionnaire, STAI scale, questionnaire for measuring the locus of control, standardized Delta Questionnaire and a demographic survey.ResultsThe analysis revealed that the level of physical aggression was positively correlated with anxiety as a state (R=0.29; P<0.001), as a trait (R=0.32; P<0.001) and with an external sense of control (R=0.27; P<0.001). The level of verbal aggression was positively and weakly correlated with the sense of control (R=0.22; P<0.05) and weakly and negatively correlated with the lie scale (R=-0.24; P<0.001). Anger, hostility and general aggression were positively correlated with anxiety as a state (R=0.36; R=0.52; R=0.45; P<0.001, respectively) and as a trait (R = 0.50; R = 0.60; R = 0.56; P<00.001).ConclusionsThe results indicate a statistically significant higher level of aggression in the group of patients diagnosed with schizophrenia compared to the control group representing the healthy population. The statistically significant differences in the patient group were observed in physical aggression, hostility, and the total aggression score. The results indicate that a higher level of aggression was observed in the subjects who placed the locus of control more externally.